Potential Blood DNA Methylation Biomarker Genes for Diagnosis of Liver Fibrosis in Patients With Biopsy-Proven Non-alcoholic Fatty Liver Disease - Sun, Qing-Feng; Tang, Liang-Jie; Wang, Ming-Jie; Zhu, Pei-Wu; Li, Yang-Yang; Ma, Hong-Lei; Huang, Ou-Yang; Hong, Liang; Li, Gang; Byrne, Christopher D.; Targher, Giovanni; Liu, Wen-Yue; et al. (Frontiers in Medicine, 2022)
Background and objective: This pilot study aimed to identify potential blood DNA methylation (BDM) biomarker genes for the diagnosis of liver fibrosis in non-alcoholic fatty liver disease (NAFLD). Methods: We included a total of 16 NAFLD patients with significant (SLF, liver fibrosis stage  2) and 16 patients with non-significant liver fibrosis (NSLF, fibrosis stages 0-1). The association between BDM and liver fibrosis was analyzed. Genes were selected based on a stepwise-filtering with CpG islands containing significant differentially methylated probes. Results: The two groups of NAFLD patients were distinguishable through t-distributed stochastic neighbor embedding analysis and unsupervised hierarchical clustering analysis based on their BDM status. BDM levels were significantly higher in the NSLF group than in the SLF group. The methylation levels in the island and shelf regions were also significantly higher in the NSLF group, as well as the methylation levels in the first exon, 3’-untranslated region, body, ExonBnd, non-intergenic region, transcription start site (TSS)1500, and TSS200 regions (all p<0.05). BDM status was associated with greater liver fibrosis, but not with age, sex, or other histological features of NASH (p<0.05). The methylation levels of the hypomethylated CpG island region of CISTR, IFT140, and RGS14 genes were significantly increased in the NSLF group compared to the SLF group (all p<0.05). Conclusions: BDM may stratify NAFLD patients with significant and non-significant liver fibrosis. The CISTR, IFT140, and RGS14 genes are potential novel candidate BDM biomarkers for liver fibrosis and these pilot data suggest further work on BDM biomarkers is warranted.